2020
DOI: 10.1101/2020.05.13.094524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the genetic basis of copper toxicity inDrosophilareveals a complex pattern of allelic, regulatory, and behavioral variation

Abstract: 1A range of heavy metals are required for normal cell function and homeostasis. Equally, 2 the anthropogenic release of heavy metals into soil and water sources presents a pervasive 3 health threat. Copper is one such metal; it functions as a critical enzymatic cofactor, but at high 4 concentrations is toxic, and can lead to the production of reactive oxygen species. Using a 5 combination of quantitative trait locus (QTL) mapping and RNA sequencing in the Drosophila 6Synthetic Population Resource (DSPR), we de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 110 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…4 and Table 2). Of these seven confirmed genes, CG11594, Cyp6w1, Cyp6a8 , and Jon65Aiv , are novel candidates, whose full role in copper biology is not yet understood, while the other three genes, Sodh-1, CG6910 , and CG32444 have prior links to the phenotype [12, 20, 55]. On the other hand, CG5966 displayed decreased mortality when knocked-down, which was not predicted by its induction on copper (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…4 and Table 2). Of these seven confirmed genes, CG11594, Cyp6w1, Cyp6a8 , and Jon65Aiv , are novel candidates, whose full role in copper biology is not yet understood, while the other three genes, Sodh-1, CG6910 , and CG32444 have prior links to the phenotype [12, 20, 55]. On the other hand, CG5966 displayed decreased mortality when knocked-down, which was not predicted by its induction on copper (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To date, there have been several studies exploring the nature of copper tolerance in natural strains of D. melanogaster, both with regard to individual genes [16,17] and to broader developmental and learning and memory processes [18,19]. Recently, Everman et al (2021) [20] took benefit of a combination of high throughput genomic and transcriptomic approaches to uncover several new copper gene candidates, using recombinant inbred lines. They found that copper resistance is genetically complex and impacted by variation in copper avoidance behavior.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations